1989
DOI: 10.1002/ijc.2910430504
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 7F7‐antigen, a human adhesion molecule identical to intercellular adhesion molecule‐1 (ICAM‐1) in human carcinomas and their stromal fibroblasts

Abstract: The 7F7-antigen is a widespread 85-kDa membrane adherence molecule involved in heterotypic adhesion between PHA-blasts and fibroblasts. Immunofluorescence analysis of COS cells transfected with clone pICAM-I indicated that 7F7-antigen is identical with ICAM-I, the ligand for the contact molecule LFA-I. We have investigated the expression of ICAM-I on several human carcinomas. Tumor cells in most carcinomas, with the exception of squamous-cell carcinomas, expressed very little ICAM-I or none at all. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
3

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 27 publications
1
39
3
Order By: Relevance
“…Our data suggest the possibility that stromal fibroblasts may indeed facilitate tumour progression, possibly invasion, and metastasis, leading to a higher rate of disease recurrence. Fibroblasts, being both activated by cytokines and at the same time producing cytokines or other soluble factors, were reported to modulate various aspects of tumour progression including proliferation or invasion (Vogetseder et al, 1989;Nakamura et al, 1997), angiogenesis (Orimo et al, 2001), or inhibition of cell death (Olumi et al, 1998). Vimentin expression is reportedly universally found in all types of fibroblasts (Skalli et al, 1989;Sappino et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest the possibility that stromal fibroblasts may indeed facilitate tumour progression, possibly invasion, and metastasis, leading to a higher rate of disease recurrence. Fibroblasts, being both activated by cytokines and at the same time producing cytokines or other soluble factors, were reported to modulate various aspects of tumour progression including proliferation or invasion (Vogetseder et al, 1989;Nakamura et al, 1997), angiogenesis (Orimo et al, 2001), or inhibition of cell death (Olumi et al, 1998). Vimentin expression is reportedly universally found in all types of fibroblasts (Skalli et al, 1989;Sappino et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies which have included ovarian adenocarcinomas scored either 5-30% of cells positive from a single tumour examined (Vogetseder et al, 1989) or found 0/15 primary tumours and 0/9 metastasis positive for ICAM-1 expression (Natali et al, 1990). While the antibody used in these studies was different to that used in this study, the data support our findings that the majority of ovarian tumours express little or no ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…There was also frequent LOH at 19p13 (28%) at a similar rate to that reported in previous studies (Amfo et al, 1995;Wang et al, 1999). We found a weak association between this LOH and loss of ICAM-1 expression, suggesting that loss of expression may also be due to LOH in some cases.Expression of ICAM-1 has previously been examined by immunohistochemistry in a variety of human neoplasms including breast cancer, lung cancer, squamous-cell carcinoma, renal cell cancer, pancreatic cancer, gastric cancer, ovarian adenocarcinoma, prostatic cancer, thyroid cancer and malignant melanoma (Johnson et al, 1989;Vogetseder et al, 1989;Natali et al, 1990;Tomita et al, 1990;Koyama et al, 1992; Schwaeble et al, 1993;Ogawa et al, 1998). Previous studies which have included ovarian adenocarcinomas scored either 5-30% of cells positive from a single tumour examined (Vogetseder et al, 1989) or found 0/15 primary tumours and 0/9 metastasis positive for ICAM-1 expression (Natali et al, 1990).…”
mentioning
confidence: 99%
“…Altogether, these results provide evidence of an important role for Ets-related transcription factors, and more particularly the PEA3 group members, in tumor cell invasion. Strong ICAM-1 expression is found in solid tumors such as melanomas and renal carcinomas and in a lesser extent in gastric, breast and colorectal carcinomas (Vogetseder et al, 1989;Natali et al, 1990;Johnson, 1991). As far as melanoma are concerned, de novo ICAM-1 expression correlates with increased risk of metastasis (Johnson et al, 1989).…”
Section: Discussionmentioning
confidence: 99%